Post - Divorce Traumatic Stress and the Christian Soul: A Psycho-Theological Approach to Inner Healing - Lie, Tan Lie; Chandra, Janto (Journal of Educational, Health and Community Psychology, 2025)
Divorce often results in profound emotional and spiritual turmoil, especially for Christians who view marriage as a divine covenant. This qualitative study explores the post-divorce traumatic experiences and inner healing processes of five Christian individuals using a psycho-theological approach. Data were collected through in-depth interviews with 5 participants using purposive sampling technique. The findings reveal recurring themes of spiritual disorientation, emotional distress marked by guilt and loss of identity, and a journey toward healing facilitated by personal faith, prayer, scripture reflection, and support from faith communities. Participants described both theological struggle and spiritual resilience, highlighting the significance of integrating psychological and spiritual frameworks in trauma recovery. This study contributes to pastoral care and Christian counseling by offering insights into the inner transformation that follows relational breakdown. It underscores the importance of faith-based coping mechanisms in navigating post-traumatic stress within a Christian worldview.